Evaluation of the rationality of using antibiotics in orthopedic surgery patients at the Cilacap Regional General Hospital using the Gyssens method - Permana, Fadli Bayu; Sofiah, Siti Asadu; Salfia, Wa Ode; Nurkholis, Fiqih (Ad-Dawaa : Journal of Pharmacy, 2024)
A fracture is a condition of severing or damage to the cartilage, bone structure, or epiphysis, which is divided into open and closed fractures. Open fractures require antibiotic therapy to prevent infection, given the high risk of infection. Evaluation of the rationality of antibiotic use is very important to ensure effective therapy and prevent side effects, ineffective treatment, high costs, and antibiotic resistance. Antibiotic resistance can increase infections that are difficult to treat and increase morbidity and mortality. This study aims to evaluate the rationality of antibiotic use in orthopedic surgery patients at Cilacap Regional Hospital using the Gyssens method. The study was observational and collected retrospective data from 55 patients who underwent orthopedic surgery for open fractures in 2023. The data used for analysis included patient identity, diagnosis, laboratory data, and antibiotic use. The results obtained were category 0 (appropriate and rational use of antibiotics) 37%, category II A (inappropriate dosage) 10%, category II B (inappropriate administration interval) 1%, category III B (administration of antibiotics too short) 9%, category IV A (presence of other more effective antibiotics) 1%, category IV C (presence of cheaper antibiotics) 39%, category VI (incomplete patient data) 4%. The conclusion shows that there are still many antibiotic prescriptions that do not meet category 0, indicating the need for improvement in the rationality of antibiotic use at Cilacap Regional Hospital.